2020
DOI: 10.1002/pssb.202000289
|View full text |Cite
|
Sign up to set email alerts
|

New Phase Transitions Driven by Soft Phonon Modes for CsPbBr3: Density Functional Theory Study

Abstract: Using first‐principles lattice dynamics calculations, new phase transitions driven by soft phonon modes in CsPbBr3, from the high‐symmetry cubic structure Pm3m to hypothetical structures, are predicted. The structural, electronic, and dielectric properties of the new phases are determined. A ferroelectric phase with Pmc21 symmetry is found to be more stable than the experimentally observed phases. It is suggested that it is a good candidate as a ground state. It is demonstrated that the out‐of‐phase rotations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…The phonon dispersion curves obtained from density functional theory and Wannier interpolation were shown in figure 4, and some soft modes could be observed on cubic halide perovskites, which indicated that they were thermodynamically unstable. Cubic perovskite was stable at high temperature and unstable at low temperature, which had been reported in previous investigation [74][75][76]. Since the mobility was mainly determined by optical phonons with highfrequency, these soft modes would not greatly affect the mobility results.…”
Section: Accuracy Of the Wannier-interpolationsupporting
confidence: 67%
“…The phonon dispersion curves obtained from density functional theory and Wannier interpolation were shown in figure 4, and some soft modes could be observed on cubic halide perovskites, which indicated that they were thermodynamically unstable. Cubic perovskite was stable at high temperature and unstable at low temperature, which had been reported in previous investigation [74][75][76]. Since the mobility was mainly determined by optical phonons with highfrequency, these soft modes would not greatly affect the mobility results.…”
Section: Accuracy Of the Wannier-interpolationsupporting
confidence: 67%
“…Here, we employ macroscopic measured properties to optimize the Landau parameters in the FE-MPF model, and we implicitly assume that the experimentally observed phase is the thermodynamically stable phase at the temperature of interest. Ab initio phonon calculations and stability analyses would validate these assumptions or reveal other more stable states [75]. This approach was out-of-scope of the current study, but future ab initio-derived data should be utilised in parameter optimization.…”
Section: Symbolmentioning
confidence: 95%